UJI AKTIVITAS ANTIBAKTERI SEDIAAN PEEL OFF MASK EKSTRAK ETANOL DAUN KELOR - Pratiwi Ishak; Fihrina Mohamad; Prisca Safriani Wicita; Nangsih Sulastri Slamet; Arlan K. Imran (JURNAL KATALISATOR, 2022)
Propionibacterium acnes is one of the bacteria that trigger acne. A popular face mask preparation today for acne skin care is the peel off Mask. The purpose of this study was to formulate ethanol extract of moringa leaves (Moringa oleifera L.) become a Peel Off mask preparation and see the antibacterial activity of the preparation against Propionibacterium acnes. This research method is quasi experimental, formulated Peel Off Mask preparation with variation of ethanol extract of moringa leaves F1 (10%), F2 (15%) and F3 (20%), then physical test (organoleptic test with hedonic scale 1-5, pH test, irritation test, spreadability test, dry time test) and antibacterial activity test with diffusion method. Data analysis of antibacterial activity test results using one way ANOVA test. The results showed organoleptic test, pH test, irritation test and drying time test F1-F3 all meet the standard. Antibacterial activity test has the greatest power is F1 17.17 mm. The result of one way anova test between F3 treatment with positive control 2 (peel Off mask Brand x®) obtained significance value (0.01) <(0.05), which means F3 has a significant difference to KP2. Conclusion; preparation peel Off Mask ethanol extract of Moringa leaves F3 is the best formula physically and has the greatest antibacterial activity of 17.17 mm (strong) against Propionibacterium acnes.